Protective role of curcumin on renal ischemia reperfusion injury via attenuating the inflammatory mediators and Caspase-3 - Liu, F-H; Ni, W-J; Wang, G-K; Zhang, J-J (Cellular and Molecular Biology, 2016)
Renal ischemia/reperfusion (I/R) damage may arise due to nephron sparing surgery in patient with a solitary kidney of restricted renal parenchymas. Apoptosis, inflammation and oxidative stress play a significant role in the expansion of renal dysfunction following renal I/R. The aim of the current investigation was to particularize the potential effect of curcumin against hypoxia induced renal injury. The albino Wistar rats divided into groups and each group contains six rats. They groups are normal control; disease control; curcumin (5 mg/kg per day) and another group orally treated with curcumin (10 mg/kg per day) for two weeks before induction of renal I/R. The renal and serum samples were collected and used for the biochemical estimation. The renal tissue was further used for the histopathological estimation. The result of the current investigation demonstrated that the curcumin significantly (P<0.01) attenuated I/R induced renal injury in a dose-dependent way. It also causes significant (P<0.01) reduction in the serum creatinine, blood urea nitrogen level and also suppressed the kidney injury molecules-1. Additionally, it also causes significant inhibition of the malonaldehyde, caspase-3, myeloperoxide, lactose dehydrogenase and interferon-gamma together with enhanced interlukin-10 content.